A robust viologen and Mn-based porous coordination polymer with two types of Lewis acid sites providing high affinity for H2O, CO2 and NH3. Issue 45 (3rd November 2017) - Leblanc, A.; Mercier, N.; Allain, M.; Dul, M.-C.; Weber, G.; Geoffroy, N.; Bellat, J.-P.; Bezverkhyy, I.
Abstract : A water stable PCP with two kinds of Lewis acid sites, open Mn 2+ cations and viologen, shows high affinity for H2 O, CO2 and NH3 . Abstract : A novel porous coordination polymer [Mn( pc3 )(H2 O)2 ]· x H2 O (3 < x < 4) is synthesized in water at pH = 7 using the anionic viologen-carboxylate ligand 4, 4′-bipyridinium, 1, 1′-bis-(2, 4-dicarboxyphenyl) ( pc3 2− ). Dehydration of the material results in the formation of open pores containing two types of accessible Lewis acid sites: exposed Mn 2+ cations and N + atoms of viologen units. Due to this property the PCP shows high affinity and capacity in the adsorption of H2 O, CO2 and NH3 . Despite the presence of strong adsorption sites this material is stable in liquid water and in gaseous NH3 .